Clinical and neuropsychological characteristics of children with epilepsy and attention-deficit/hyperactivity disorder. (October 2021) - Park, Kee Jeong; Kim, Min-Jee; Yum, Mi-Sun; Ko, Tae-Sung; Kim, Hyo-Won
Highlights: Children with both epilepsy and ADHD had poorer response inhibition than children with epilepsy alone. Compared with children with epilepsy alone, children with both epilepsy and ADHD had more disruptive behaviors, less reciprocal social interactions, and higher parenting stress. Proper identification of comorbid ADHD in children with epilepsy could be useful for improving their clinical functioning. Abstract: Objectives: This study aimed to explore the clinical and neuropsychological characteristics—cognition, behavior, parenting-related stress, and sleep—of children with epilepsy, attention-deficit/hyperactivity disorder (ADHD), or both. Methods: We retrospectively reviewed the electronic medical records of 33 children with epilepsy and ADHD, 113 with epilepsy alone, and 294 with ADHD alone. The children were required to complete the Advanced Test of Attention (ATA), and their parents completed the ADHD Rating Scale (ARS), Child Behavior Checklist (CBCL), Children's Sleep Habits Questionnaire (CSHQ), Disruptive Behavior Disorder (DBD) Scale (DBD), Social Responsiveness Scale (SRS), and Parenting Stress Index-Short Form (PSI-SF). Results: Auditory Commission Errors made during the ATA were higher in children with epilepsy and ADHD than in those with epilepsy alone. On the SRS, all the subscales except Social Awareness were significantly higher in children with epilepsy and ADHD or ADHD alone than in those with epilepsy alone. The Oppositional Defiant and Conduct Disorder subscales on DBD, Attention Problems, and Aggressive Behaviors on CBCL were significantly higher in children with both epilepsy and ADHD than in those with epilepsy alone. The Parent-Child Dysfunctional Interaction subscales on the PSI-SF were significantly greater in children with both epilepsy and ADHD than in those with epilepsy alone. The subscales on the CSHQ did not significantly differ between children with both epilepsy and ADHD and those with epilepsy alone. Conclusions: In children with epilepsy, comorbid ADHD was associated with negative effects on response inhibition, aggressive behavior, and parenting-related stress.